Full publication of results initially presented in abstracts - Scherer, Roberta W; Meerpohl, Joerg J; Pfeifer, Nadine; Schmucker, Christine; Schwarzer, Guido; von Elm, Erik (Cochrane database of systematic reviews, 2018)
Abstracts of presentations at scientific meetings are usually available only in conference proceedings. If subsequent full publication of results reported in these abstracts is based on the magnitude or direction of the results, publication bias may result. Publication bias creates problems for those conducting systematic reviews or relying on the published literature for evidence about health and social care. To systematically review reports of studies that have examined the proportion of meeting abstracts and other summaries that are subsequently published in full, the time between meeting presentation and full publication, and factors associated with full publication. We searched MEDLINE, Embase, the Cochrane Library, Science Citation Index, reference lists, and author files. The most recent search was done in February 2016 for this substantial update to our earlier Cochrane Methodology Review (published in 2007). We included reports of methodology research that examined the proportion of biomedical results initially presented as abstracts or in summary form that were subsequently published. Searches for full publications had to be at least two years after meeting presentation. Two review authors extracted data and assessed risk of bias. We calculated the proportion of abstracts published in full using a random-effects model. Dichotomous variables were analyzed using risk ratio (RR), with multivariable models taking into account various characteristics of the reports. We assessed time to publication using Kaplan-Meier survival analyses. Combining data from 425 reports (307,028 abstracts) resulted in an overall full publication proportion of 37.3% (95% confidence interval (CI), 35.3% to 39.3%) with varying lengths of follow-up. This is significantly lower than that found in our 2007 review (44.5%. 95% CI, 43.9% to 45.1%). Using a survival analyses to estimate the proportion of abstracts that would be published in full by 10 years produced proportions of 46.4% for all studies; 68.7% for randomized and controlled trials and 44.9% for other studies. Three hundred and fifty-three reports were at high risk of bias on one or more items, but only 32 reports were considered at high risk of bias overall.Forty-five reports (15,783 abstracts) with 'positive' results (defined as any 'significant' result) showed an association with full publication (RR = 1.31; 95% CI 1.23 to 1.40), as did 'positive' results defined as a result favoring the experimental treatment (RR =1.17; 95% CI 1.07 to 1.28) in 34 reports (8794 abstracts). Results emanating from randomized or controlled trials showed the same pattern for both definitions (RR = 1.21; 95% CI 1.10 to 1.32 (15 reports and 2616 abstracts) and RR = 1.17; 95% CI, 1.04 to 1.32 (13 reports and 2307 abstracts), respectively.Other factors associated with full publication include oral presentation (RR = 1.46; 95% CI 1.40 to 1.52; studied in 143 reports with 115,910 abstracts); acceptance for meeting presentation (RR = 1.65; 95% CI 1.48 to 1.85; 22 reports with 22,319 abstracts); randomized trial design (RR = 1.51; 95% CI 1.36 to 1.67; 47 reports with 28,928 abstracts); and basic research (RR = 0.78; 95% CI 0.74 to 0.82; 92 reports with 97,372 abstracts). Abstracts originating at an academic setting were associated with full publication (RR = 1.60; 95% CI 1.34 to 1.92; 34 reports with 16,913 abstracts), as were those considered to be of higher quality (RR = 1.46; 95% CI 1.23 to 1.73; 12 reports with 3364 abstracts), or having high impact (RR = 1.60; 95% CI 1.41 to 1.82; 11 reports with 6982 abstracts). Sensitivity analyses excluding reports that were abstracts themselves or classified as having a high risk of bias did not change these findings in any important way.In considering the reports of the methodology research that we included in this review, we found that reports published in English or from a native English-speaking country found significantly higher proportions of studies published in full, but that there was no association with year of report publication. The findings correspond to a proportion of abstracts published in full of 31.9% for all reports, 40.5% for reports in English, 42.9% for reports from native English-speaking countries, and 52.2% for both these covariates combined. More than half of results from abstracts, and almost a third of randomized trial results initially presented as abstracts fail to be published in full and this problem does not appear to be decreasing over time. Publication bias is present in that 'positive' results were more frequently published than 'not positive' results. Reports of methodology research written in English showed that a higher proportion of abstracts had been published in full, as did those from native English-speaking countries, suggesting that studies from non-native English-speaking countries may be underrepresented in the scientific literature. After the considerable work involved in adding in the more than 300 additional studies found by the February 2016 searches, we chose not to update the search again because additional searches are unlikely to change these overall conclusions in any important way.